2016
DOI: 10.1007/s00535-016-1241-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammatory bowel disease on Japanese patients’ quality of life: results of a patient questionnaire survey

Abstract: BackgroundInflammatory bowel disease (IBD) has a significant negative impact on quality of life (QOL); however, the direct impact of IBD on several aspects of patients’ lives is unknown. The IMPACT survey was conducted in Europe in 2010–2011 to determine this impact. We conducted the IMPACT survey in Japan and compared the results between subgroups of patients with ulcerative colitis (UC) and Crohn’s disease (CD).MethodsThe 52-item IMPACT survey questionnaire assessing treatment and the impact of IBD on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 16 publications
3
50
0
2
Order By: Relevance
“…In the IMPACT survey of 4,670 patients with IBD from 25 European countries, 64% of respondents believed that their gastroenterologist should have asked more probing questions to understand their disease [ 28 ]. A similar response (68.6%) to the same question was found when the IMPACT survey was repeated in 172 Japanese patients with IBD [ 27 ]. Similarly, in survey by the European Federation of Crohn’s and Ulcerative Colitis Associations (EFCCA), 47.8% of 5,576 patients with IBD reported that their physician did not ask about the impact of symptoms on their quality of life [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the IMPACT survey of 4,670 patients with IBD from 25 European countries, 64% of respondents believed that their gastroenterologist should have asked more probing questions to understand their disease [ 28 ]. A similar response (68.6%) to the same question was found when the IMPACT survey was repeated in 172 Japanese patients with IBD [ 27 ]. Similarly, in survey by the European Federation of Crohn’s and Ulcerative Colitis Associations (EFCCA), 47.8% of 5,576 patients with IBD reported that their physician did not ask about the impact of symptoms on their quality of life [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
“…Inadequate sharing of information between healthcare professionals was reported by nearly a quarter of the patients (22.4%; P <0.001). Dissatisfaction with patient-provider communication has been reported in other patient surveys [ 6 , 22 , 27 , 28 ]. In the IMPACT survey of 4,670 patients with IBD from 25 European countries, 64% of respondents believed that their gastroenterologist should have asked more probing questions to understand their disease [ 28 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…15,16 The incidence and prevalence of UC in Asian countries have been rapidly increasing; [17][18][19] despite this, psychosocial assessments are overlooked in practice, and only a few studies have addressed these issues. 7,20,21 In this background, we aimed to comprehensively quantify the burden of psychosocial distress and to identify significant predictors affecting HRQL among newly-diagnosed patients with UC. All patients were affiliated with the MOSAIK (moderate-to-severe ulcerative colitis in Korea) cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…troublesome symptoms, such as abdominal pain, diarrhea, hematochezia, fever, perianal lesions, weight loss, and fatigue, which can impact markedly on patient quality of life (QoL) [1][2][3][4][5]. In addition to enteric complications (eg, stricture, abscess, fistula, hemorrhage), CD may also result in extraintestinal inflammatory complications in the joints, skin, eyes, mouth, and other organ systems [1][2][3].…”
mentioning
confidence: 99%